Environment-friendly coating for low VOCs coated white board paper and preparation process thereof
Patent Information
- Application Number
- CN202611227103.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]然而目前市场上的低VOCs涂料常面临性能与环保难以兼顾的技术矛盾
本发明采用水性丙烯酸乳液和羧基丁苯胶乳作为主要基料,从源头上避免了苯类、甲醛等有毒挥发性有机物的使用,有效降低了涂料的VOCs含量≤20g/L。更重要的是,本发明通过改性淀粉的特定制备及其与丙烯酸丁酯、过氧化苯甲酸叔丁酯、脱氢乙酸等组分的协同配合,攻克了低VOCs涂料性能不佳的技术瓶颈。本发明提供的涂料在涂布白板纸后,不仅表现出1.7%极低的吸水率,展现出优异的防水性能;同时,其光泽度高达82和耐折性均显著优于对比例,综合性能得到全面提升。
Smart Images

Figure CN122980262A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of whiteboard paper preparation technology, specifically to an environmentally friendly coating for low-VOC coated whiteboard paper and its preparation process. Background Technology
[0002] Coated whiteboard paper is a material used for packaging food, cosmetics, pharmaceuticals, daily necessities, etc., formed by coating a layer of pigment (usually white, to facilitate subsequent printing and processing) onto a base paper material.
[0003] Coated whiteboard paper achieves its packaging function not only through its inherent properties but also through external coatings that provide aesthetic appeal, folding resistance, and water resistance. However, existing coatings for coated whiteboard paper often contain volatile organic compounds (VOCs) such as benzene, formaldehyde, and vinyl chloride. These substances evaporate into the atmosphere after the coating is applied, polluting indoor air quality. Long-term exposure to these pollutants may cause skin irritation, respiratory damage, hematopoietic system disorders, and nervous system diseases, and may even pose a cancer risk. Therefore, for environmental protection and the safety of food and other product packaging, it is crucial to use low-VOC, environmentally friendly coatings for coated whiteboard paper.
[0004] However, low-VOC coatings currently on the market often face a technical contradiction between performance and environmental protection. Specifically, to reduce VOCs, the amount of solvent-based resins and harmful additives used in coatings is limited, which often leads to a decrease in coating leveling and film density, resulting in reduced gloss, poor flexural strength leading to cracking, and high water absorption causing insufficient waterproofing. Therefore, how to effectively reduce VOC content while ensuring that coatings possess excellent gloss, flexural strength, and low water absorption is a technical challenge that urgently needs to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides an environmentally friendly coating for coating whiteboard paper with low VOCs and its preparation process, which effectively ensures good gloss of the coating while reducing VOCs and improving the overall environmental performance.
[0006] To achieve the above objectives, the present invention provides the following technical solution: An environmentally friendly coating for coating whiteboard paper with low VOCs, the coating being composed of the following components by weight: 30-40 parts of water-based acrylic emulsion, 10-15 parts of carboxylated styrene-butadiene latex, 10-15 parts of kaolin, 10-15 parts of calcium carbonate, 2-6 parts of modified starch, 2-6 parts of additives, 2-4 parts of propylene glycol, 0.4-0.6 parts of butyl acrylate, 0.2-0.6 parts of tert-butyl peroxide, 0.1-0.4 parts of dehydroacetic acid, and 2-10 parts of deionized water; wherein the modified starch is obtained by gelatinizing starch, activating it with urea, and then further mixing it with lactic acid for graft copolymerization.
[0007] Preferably, the specific preparation method of the modified starch includes the following steps: S1. Mix corn starch with water and heat to 80-90℃ for 20-30 minutes to gelatinize and obtain starch slurry for later use. S2. Add 1%-3% of urea (total mass of corn starch) to the starch slurry and activate it by stirring in a water bath at 50-65℃ for 15-25 minutes to obtain activated slurry for later use. S3. Prepare a lactic acid aqueous solution with a lactic acid concentration of 20%-25%. Mix the lactic acid aqueous solution with the activated slurry at a mass ratio of 5-6:1 and stir evenly. Then add NaOH to the system to adjust the NaOH concentration to 0.2-0.3 mol / L. Stir the reaction in an inert gas environment for 4-6 hours to obtain the reaction mixture for later use. S4. The reaction mixture was repeatedly stirred and washed with acetone and filtered. The filtered product was dried to obtain modified starch.
[0008] Preferably, the stirring speed in step S2 is 80-400 r / min.
[0009] Preferably, the temperature of the stirring reaction in step S3 is 90-110℃, and the stirring speed is 120-180 r / min.
[0010] Preferably, the drying temperature in step S4 is 35-55°C.
[0011] Preferably, the additive is a mixture of dispersant, defoamer and thickener in a mass ratio of 1-2:0.2-0.4:0.5-1.
[0012] The preparation process of the above-mentioned environmentally friendly coatings includes the following steps: (1) Mix butyl acrylate, tert-butyl peroxide and dehydroacetic acid with propylene glycol and stir until homogeneous. Then add modified starch and deionized water and stir at a water bath temperature of 60-70℃ to obtain a preliminary mixture. (2) Adjust the pH of the water-based acrylic emulsion and carboxylated styrene-butadiene latex to 8.5-9.0, then mix them and pressurize them to 1-2 MPa and stir them thoroughly. Then add kaolin and calcium carbonate and mix them thoroughly to obtain a mixed resin material for later use. (3) Add additives to the mixed resin material, stir evenly, add the preliminary mixture, continue stirring and let stand to obtain environmentally friendly coating.
[0013] Preferably, the stirring speed in step (1) is 200-600 r / min, and the stirring time is 15-30 min.
[0014] Preferably, in step (2), the stirring speed is 1200-1600 r / min, the stirring time is 80-120 min, and the temperature is controlled at 25-35℃ during stirring.
[0015] Preferably, the stirring speed in step (3) is 80-120 r / min, and the stirring speed is 200-400 r / min.
[0016] The modified starch of this invention is prepared by a specific process of gelatinization-urea activation-lactic acid graft copolymerization. First, after the corn starch is gelatinized, the hydrogen bonds between its molecular chains are weakened and the crystal structure is destroyed, providing more active sites for subsequent modification. Secondly, the addition of urea acts as a plasticizer and breaks hydrogen bonds, making starch chain segments more mobile. The amino groups in the urea molecule can form new hydrogen bonds with the starch hydroxyl groups, playing a space-occupying role and effectively preventing the re-aggregation of starch chains, thus achieving an activation effect. Finally, under the action of the alkaline catalyst NaOH, lactic acid undergoes a graft copolymerization reaction with the activated starch hydroxyl groups, introducing long-chain polylactic acid (PLA) side chains onto the starch molecule backbone. When this modified starch is applied to coatings, it exhibits amphiphilic properties: the PLA side chains have excellent compatibility with the acrylate components in the system, such as aqueous acrylic emulsions and butyl acrylate, while the starch backbone forms good interfacial bonding with carboxylated styrene-butadiene latex, inorganic fillers such as kaolin, and calcium carbonate. This "bridging" effect significantly improves the overall uniformity and film density of the coating, thus providing a foundation for simultaneously improving the coating's gloss, flexural strength, and water resistance.
[0017] In this invention, butyl acrylate forms a unique synergistic effect with the initiator tert-butyl peroxide, the multifunctional additive dehydroacetic acid, and the modified starch: Under heating and in the presence of the initiator, butyl acrylate can undergo a certain degree of grafting or cross-linking reaction with the unsaturated groups in aqueous acrylic emulsions and carboxylated styrene-butadiene latex, forming a denser three-dimensional network structure. The addition of dehydroacetic acid serves two purposes: firstly, as an environmentally friendly antifungal agent; secondly, the carbonyl and acetoacetyl groups in its molecular structure can coordinate or hydrogen bond with the hydroxyl groups of the modified starch and the metal ions on the surface of the inorganic filler, further enhancing the organic-inorganic interface bonding. This synergistic system forms a dense cross-linked network that effectively blocks the penetration of water molecules, reducing water absorption; the uniform and strong interfacial bonding reduces stress concentration points, significantly improving the flexibility and folding resistance of the coating; simultaneously, the uniform film surface ensures the uniformity of light reflection, thereby enhancing gloss.
[0018] This invention provides an environmentally friendly coating for low-VOC coating of whiteboard paper and its preparation process, which has the following advantages compared with the prior art: This invention uses water-based acrylic emulsion and carboxylated styrene-butadiene latex as the main base materials, avoiding the use of toxic volatile organic compounds such as benzene and formaldehyde from the source, effectively reducing the VOCs content of the coating to ≤20g / L. More importantly, this invention overcomes the technical bottleneck of poor performance of low-VOCs coatings by specifically preparing modified starch and its synergistic effect with components such as butyl acrylate, tert-butyl peroxide, and dehydroacetic acid. The coating provided by this invention, after being coated on whiteboard paper, not only exhibits an extremely low water absorption rate of 1.7%, demonstrating excellent waterproof performance, but also boasts a gloss level as high as 82 and significantly better folding endurance than the comparative example, resulting in a comprehensive improvement in overall performance. Attached Figure Description
[0019] Figure 1 This is a schematic diagram comparing the gloss of the coatings prepared in Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 of the present invention. Figure 2 This is a schematic diagram comparing the number of folds required to cause cracks when whiteboard paper is folded after being coated with the coatings prepared in Embodiment 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 of the present invention. Figure 3 This is a schematic diagram comparing the water absorption rates of the coatings prepared in Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 of the present invention. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] The aqueous acrylic emulsion used in the following examples was purchased from Shenzhen Feizhouniu Industrial Co., Ltd., product number 8000S; the carboxylated styrene-butadiene latex was BASF carboxylated styrene-butadiene latex SD417; the dispersant was sodium maleic acid-acrylic acid copolymer (MA-AA·Na) dispersant, purchased from Shandong Zhengtai New Materials Co., Ltd.; the defoamer was BYK-1799 defoamer; and the thickener was hydroxyethyl cellulose. The additives were obtained by mixing the dispersant, defoamer, and thickener in a mass ratio of 1.5:0.3:0.8.
[0022] Example 1:
[0023] 1. Preparation of modified starch: 1.1 Modified starch A: (1) Mix corn starch with 5 times its volume of water and heat to 85°C for 25 minutes to gelatinize and obtain starch slurry for later use; (2) Add 2% of the total mass of corn starch and urea to the starch slurry, and stir and activate it at 120 r / min at 60℃ for 20 min to obtain activated slurry for later use; (3) Prepare a lactic acid aqueous solution with a lactic acid concentration of 25%, mix the lactic acid aqueous solution with the activated slurry at a mass ratio of 6:1 and stir evenly, then add NaOH to the system to adjust the NaOH concentration in the system to 0.3 mol / L, and stir the reaction at 160 r / min for 5 h at 100℃ in a nitrogen atmosphere to obtain the reaction mixture for later use; (4) The reaction mixture was repeatedly stirred and washed with acetone and filtered. The filtered product was dried at 40°C to obtain modified starch A.
[0024] 1.2 Modified Starch B: Corn starch was mixed with 5 times its volume of water and heated to 85°C for 25 minutes to gelatinize. The resulting starch slurry was then dried at 40°C to obtain modified starch B.
[0025] 1.3 Modified starch C: (1) Mix corn starch with 5 times the volume of water and add 2% of the total mass of corn starch with urea. Stir and activate the mixture at 60°C and 120 r / min for 20 min to obtain activated slurry for later use. (2) Prepare a lactic acid aqueous solution with a lactic acid concentration of 25%. Mix the lactic acid aqueous solution with the activated slurry at a mass ratio of 6:1 and stir evenly. Then add NaOH to the system to adjust the NaOH concentration in the system to 0.3 mol / L. Stir the reaction at 160 r / min for 5 h at 100 °C in a nitrogen atmosphere to obtain the reaction mixture for later use. (3) The reaction mixture was repeatedly stirred and washed with acetone and filtered. The filtered product was dried at 40°C to obtain modified starch C.
[0026] Example 2:
[0027] Preparation of coatings: (1) Prepare the following materials according to the following weight parts: 35 parts of water-based acrylic emulsion, 13 parts of carboxylated styrene-butadiene latex, 13 parts of kaolin, 13 parts of calcium carbonate, 4 parts of modified starch A, 4 parts of additives, 3 parts of propylene glycol, 0.5 parts of butyl acrylate, 0.4 parts of tert-butyl peroxide, 0.3 parts of dehydroacetic acid, and 6 parts of deionized water; (2) Mix butyl acrylate, tert-butyl peroxide and dehydroacetic acid with propylene glycol and stir at 400 r / min for 20 min. Then add modified starch A and deionized water and stir at 65°C in a water bath to obtain a preliminary mixture. (3) Adjust the pH of the water-based acrylic emulsion and carboxylated styrene-butadiene latex to 8.5, then mix them and pressurize to 1.52 MPa. Control the temperature at 30°C and stir thoroughly at 1400 r / min for 100 min. Then add kaolin and calcium carbonate and continue to mix evenly to obtain the mixed resin material for later use. (4) Add additives to the mixed resin material, stir evenly at a speed of 100 r / min, add the preliminary mixture, adjust the speed to 400 r / min and continue stirring for 20 min, and then let it stand to obtain an environmentally friendly coating.
[0028] Comparative Example 1: Preparation of coatings: (1) Prepare the following materials according to the following weight parts: 35 parts of water-based acrylic emulsion, 13 parts of carboxylated styrene-butadiene latex, 13 parts of kaolin, 13 parts of calcium carbonate, 4 parts of modified starch B, 4 parts of additives, 3 parts of propylene glycol, 0.5 parts of butyl acrylate, 0.4 parts of tert-butyl peroxide, 0.3 parts of dehydroacetic acid, and 6 parts of deionized water; (2) Mix butyl acrylate, tert-butyl peroxide and dehydroacetic acid with propylene glycol and stir at 400 r / min for 20 min. Then add modified starch B and deionized water and stir at 65℃ water bath temperature to obtain a preliminary mixture. (3) Adjust the pH of the water-based acrylic emulsion and carboxylated styrene-butadiene latex to 8.5, then mix them and pressurize to 1.52 MPa. Control the temperature at 30°C and stir thoroughly at 1400 r / min for 100 min. Then add kaolin and calcium carbonate and continue to mix evenly to obtain the mixed resin material for later use. (4) Add additives to the mixed resin material, stir evenly at a speed of 100 r / min, add the preliminary mixture, adjust the speed to 400 r / min and continue stirring for 20 min, and then let it stand to obtain an environmentally friendly coating.
[0029] Comparative Example 2: Preparation of coatings: (1) Prepare the following materials according to the following weight parts: 35 parts of water-based acrylic emulsion, 13 parts of carboxylated styrene-butadiene latex, 13 parts of kaolin, 13 parts of calcium carbonate, 4 parts of modified starch C, 4 parts of additives, 3 parts of propylene glycol, 0.5 parts of butyl acrylate, 0.4 parts of tert-butyl peroxide, 0.3 parts of dehydroacetic acid, and 6 parts of deionized water; (2) Mix butyl acrylate, tert-butyl peroxide and dehydroacetic acid with propylene glycol and stir at 400 r / min for 20 min. Then add modified starch C and deionized water and stir at 65℃ water bath temperature to obtain a preliminary mixture. (3) Adjust the pH of the water-based acrylic emulsion and carboxylated styrene-butadiene latex to 8.5, then mix them and pressurize to 1.52 MPa. Control the temperature at 30°C and stir thoroughly at 1400 r / min for 100 min. Then add kaolin and calcium carbonate and continue to mix evenly to obtain the mixed resin material for later use. (4) Add additives to the mixed resin material, stir evenly at a speed of 100 r / min, add the preliminary mixture, adjust the speed to 400 r / min and continue stirring for 20 min, and then let it stand to obtain an environmentally friendly coating.
[0030] Comparative Example 3: Preparation of coatings: (1) Prepare the following materials according to the following weight parts: 35 parts of water-based acrylic emulsion, 13 parts of carboxylated styrene-butadiene latex, 13 parts of kaolin, 13 parts of calcium carbonate, 4 parts of modified starch A, 4 parts of additives, 3 parts of propylene glycol, 0.5 parts of butyl acrylate, 0.4 parts of tert-butyl peroxide, and 6 parts of deionized water. (2) Mix butyl acrylate and tert-butyl peroxide with propylene glycol and stir at 400 r / min for 20 min. Then add modified starch A and deionized water and stir at 65°C water bath temperature to obtain a preliminary mixture. (3) Adjust the pH of the water-based acrylic emulsion and carboxylated styrene-butadiene latex to 8.5, then mix them and pressurize to 1.52 MPa. Control the temperature at 30°C and stir thoroughly at 1400 r / min for 100 min. Then add kaolin and calcium carbonate and continue to mix evenly to obtain the mixed resin material for later use. (4) Add additives to the mixed resin material, stir evenly at a speed of 100 r / min, add the preliminary mixture, adjust the speed to 400 r / min and continue stirring for 20 min, and then let it stand to obtain an environmentally friendly coating.
[0031] Comparative Example 4: Preparation of coatings: (1) Prepare the following materials according to the following weight parts: 35 parts of water-based acrylic emulsion, 13 parts of carboxylated styrene-butadiene latex, 13 parts of kaolin, 13 parts of calcium carbonate, 4 parts of modified starch A, 4 parts of additives, 3 parts of propylene glycol, 0.5 parts of butyl acrylate, 0.4 parts of tert-butyl peroxide, 0.3 parts of dehydroacetic acid, and 6 parts of deionized water; (2) Mix butyl acrylate, tert-butyl peroxide and dehydroacetic acid with propylene glycol and stir at 400 r / min for 20 min. Then add modified starch A and deionized water and stir at 65°C in a water bath to obtain a preliminary mixture. (3) Adjust the pH of the water-based acrylic emulsion and carboxylated styrene-butadiene latex to 8.5, then mix them, control the temperature at 30°C, and stir thoroughly at 1400 r / min for 100 min. Then add kaolin and calcium carbonate and continue to mix evenly to obtain the mixed resin material for later use. (4) Add additives to the mixed resin material, stir evenly at a speed of 100 r / min, add the preliminary mixture, adjust the speed to 400 r / min and continue stirring for 20 min, and then let it stand to obtain an environmentally friendly coating.
[0032] experiment: 1. The final VOCs content of the coatings obtained in each group of examples and comparative examples was tested (the test method refers to GB / T23985-2009). The specific test method is as follows: The density of each group of coatings was determined, and the moisture content was calculated. A 1g sample of each group of coatings was baked at 105±2℃ for 1 hour. The residue was determined as non-volatile matter and weighed. The content of non-volatile matter, i.e., VOCs content, was calculated using the following formula: VOCs (g / L) = (100% - Non-volatile matter content (%) - Moisture content (%)) × Coating density (g / mL) × 10.
[0033] The specific results are shown in Table 1 below: Table 1
[0034] As shown in Table 1, the VOCs content of each group of coatings meets the limit standard for low-VOCs coatings (≤20g / L), proving the effectiveness of the water-based system-based technical solution of this invention in source reduction. Further comparison reveals that Example 2, which uses the complete technical solution of this invention, has a VOCs content of 12.3g / L, significantly lower than the 15.8~18.7g / L of the comparative examples. This indicates that the polar groups introduced by the modified starch after urea activation and lactic acid grafting in this invention can form a stable hydrogen bond network with components such as dehydroacetic acid, effectively "locking in" residual free small molecules in the system. This achieves a significant reduction in VOCs while maintaining excellent gloss, folding endurance, and low water absorption (see Tables 2-4). This differentiated data fully demonstrates the synergistic effect of the components of this invention in terms of environmental performance. That is, under the premise of meeting the low-VOCs standard, the specific formulation and process of this invention can control the VOCs content at an even lower level, achieving unexpected technical effects.
[0035] 2. Select the same batch of whiteboard paper (200g / m²). 2 A layer of coating (10g / m²) is applied to the surface of the whiteboard paper. 2 After drying, the gloss of the coating was tested (60° angle, measured with a gloss meter). The specific results are shown in Table 2 below. Figure 1 As shown: Table 2
[0036] As shown in Table 2, Example 2, which adopts the complete technical solution of the present invention, has a coating gloss of 82 that is significantly better than all comparative examples, demonstrating the synergistic effect of each component and preparation process on improving gloss.
[0037] 3. Repeated folding experiments were conducted on the coated whiteboard paper. With the coated side as the front, the whiteboard paper was folded 180° towards the front and then folded 180° towards the back. This constituted one complete folding experiment. The number of folding experiments required for each group of coated whiteboard paper to develop cracks on the coated surface was measured. Specific results are shown in Table 3 below. Figure 2 As shown: Table 3
[0038] As shown in Table 3, the flexural endurance of Example 2 of the present invention (41 folds) is far superior to that of the comparative examples, which directly proves the synergistic effect of modified starch, dehydroacetic acid, and specific preparation process in improving the flexibility and crack resistance of the coating.
[0039] 4. The water absorption rate of each group of coatings was tested. In order to reduce the interference of the substrate on the test results, glass plates of the same specification were selected as the substrates to coat each group of coatings (specification 25cm×25cm). After coating, the coatings were dried to constant weight as samples. The mass of each group of samples after drying was weighed using a high-precision analytical balance and recorded as the initial mass (m0).
[0040] Place each sample vertically into room temperature deionized water, ensuring the coating surface is completely submerged and free of air bubbles. Soak for 24 hours, then remove the sample with tweezers and quickly blot dry the surface moisture with filter paper (do this within 2 minutes to minimize the impact of moisture evaporation on the results).
[0041] Immediately weigh the sample after it has been dried and record the mass as the mass after immersion in water (m1).
[0042] Calculate the water absorption rate: Water absorption rate (%) = (m1-m0) / m0 × 100%.
[0043] The specific results are shown in Table 4 and Figure 3 As shown: Table 4
[0044] Table 4 shows that the coating of Example 2 of the present invention has the lowest water absorption rate of 1.7%, demonstrating its excellent waterproof performance. In contrast, the comparative examples that omit any component or process feature of the present invention all show significantly higher water absorption rates, which fully demonstrates the synergistic effect of the various technical features of the present invention in achieving low water absorption.
[0045] In summary, the experimental results show that, under the premise of achieving low VOCs, only Example 2 can simultaneously achieve the highest gloss, best folding endurance, and lowest water absorption. This indicates that the present invention, through the synergistic effect of specific modified starch, functional additives, and preparation processes, successfully solves the technical problem of insufficient performance of low VOCs coatings, achieving unexpected technical results.
[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An environmentally friendly coating for coating whiteboard paper with low VOCs, characterized in that, The coating is composed of the following components by weight: 30-40 parts of water-based acrylic emulsion, 10-15 parts of carboxylated styrene-butadiene latex, 10-15 parts of kaolin, 10-15 parts of calcium carbonate, 2-6 parts of modified starch, 2-6 parts of additives, 2-4 parts of propylene glycol, 0.4-0.6 parts of butyl acrylate, 0.2-0.6 parts of tert-butyl peroxide, 0.1-0.4 parts of dehydroacetic acid, and 2-10 parts of deionized water; The modified starch is prepared by gelatinizing starch, activating it with urea, and then further mixing it with lactic acid for graft copolymerization.
2. The environmentally friendly coating according to claim 1, characterized in that, The specific preparation method of the modified starch includes the following steps: S1. Mix corn starch with water and heat to 80-90℃ for 20-30 minutes to gelatinize and obtain starch slurry for later use. S2. Add 1%-3% of urea (total mass of corn starch) to the starch slurry, and activate it by stirring in a water bath at 50-65℃ for 15-25 minutes to obtain activated slurry for later use. S3. Prepare a lactic acid aqueous solution with a lactic acid concentration of 20%-25%. Mix the lactic acid aqueous solution with the activated slurry at a mass ratio of 5-6:1 and stir evenly. Then add NaOH to the system to adjust the NaOH concentration to 0.2-0.3 mol / L. Stir the reaction in an inert gas environment for 4-6 hours to obtain the reaction mixture for later use. S4. The reaction mixture was repeatedly stirred and washed with acetone and filtered. The filtered product was dried to obtain modified starch.
3. The environmentally friendly coating according to claim 2, characterized in that: The stirring speed during step S2 is 80-400 r / min.
4. The environmentally friendly coating according to claim 2, characterized in that: In step S3, the temperature of the stirring reaction is 90-110℃, and the stirring speed is 120-180 r / min.
5. The environmentally friendly coating according to claim 2, characterized in that: The drying temperature in step S4 is 35-55℃.
6. The environmentally friendly coating according to claim 1, characterized in that: The additives are obtained by mixing dispersants, defoamers, and thickeners in a mass ratio of 1-2:0.2-0.4:0.5-1.
7. A preparation process for an environmentally friendly coating as described in any one of claims 1-6, characterized in that, The preparation process includes the following steps: (1) Mix butyl acrylate, tert-butyl peroxide and dehydroacetic acid with propylene glycol and stir until homogeneous. Then add modified starch and deionized water and stir at a water bath temperature of 60-70℃ to obtain a preliminary mixture. (2) Adjust the pH of the water-based acrylic emulsion and carboxylated styrene-butadiene latex to 8.5-9.0, then mix them and pressurize them to 1-2 MPa and stir them thoroughly. Then add kaolin and calcium carbonate and mix them thoroughly to obtain a mixed resin material for later use. (3) Add additives to the mixed resin material, stir evenly, add the preliminary mixture, continue stirring and let stand to obtain environmentally friendly coating.
8. The preparation process according to claim 7, characterized in that: In step (1), the stirring speed is 200-600 r / min and the stirring time is 15-30 min.
9. The preparation process according to claim 7, characterized in that: In step (2), the stirring speed is 1200-1600 r / min and the stirring time is 80-120 min, and the temperature is controlled at 25-35℃ during stirring.
10. The preparation process according to claim 7, characterized in that: In step (3), the stirring speed is 80-120 r / min, and the stirring speed is 200-400 r / min.